Evidence for time-of-day dependent effect of neurotoxic dorsomedial hypothalamic lesions on food anticipatory circadian rhythms in rats. - Glenn J Landry; Brianne A Kent; Danica F Patton; Mark Jaholkowski; Elliott G Marchant; Ralph E Mistlberger (PLoS ONE, 2011)
The dorsomedial hypothalamus (DMH) is a site of circadian clock gene and immediate early gene expression inducible by daytime restricted feeding schedules that entrain food anticipatory circadian rhythms in rats and mice. The role of the DMH in the expression of anticipatory rhythms has been evaluated using different lesion methods. Partial lesions created with the neurotoxin ibotenic acid (IBO) have been reported to attenuate food anticipatory rhythms, while complete lesions made with radiofrequency current leave anticipatory rhythms largely intact. We tested a hypothesis that the DMH and fibers of passage spared by IBO lesions play a time-of-day dependent role in the expression of food anticipatory rhythms. Rats received intra-DMH microinjections of IBO and activity and body temperature (T(b)) rhythms were recorded by telemetry during ad-lib food access, total food deprivation and scheduled feeding, with food provided for 4-h/day for 20 days in the middle of the light period and then for 20 days late in the dark period. During ad-lib food access, rats with DMH lesions exhibited a lower amplitude and mean level of light-dark entrained activity and T(b) rhythms. During the daytime feeding schedule, all rats exhibited food anticipatory activity and T(b) rhythms that persisted during 2 days without food in constant dark. In some rats with partial or total DMH ablation, the magnitude of the anticipatory rhythm was weak relative to most intact rats. When mealtime was shifted to the late night, the magnitude of the food anticipatory activity rhythms in these cases was restored to levels characteristic of intact rats. These results confirm that rats can anticipate scheduled daytime or nighttime meals without the DMH. Improved anticipation at night suggests a modulatory role for the DMH in the expression of food anticipatory activity rhythms during the daily light period, when nocturnal rodents normally sleep.